\(\dfrac{5}{6}.18\dfrac{2}{3}-\dfrac{5}{6}.6\dfrac{2}{3}\)
\(\dfrac{3}{5}+\dfrac{1}{2}+\dfrac{8}{15}\)
\(\dfrac{6}{9}+\dfrac{14}{18}-\dfrac{5}{6}\)
\(\dfrac{9}{20}-\dfrac{3}{5}:\dfrac{4}{1}\)
\(\dfrac{1}{6}+\dfrac{2}{3}\) x \(\dfrac{8}{9}\)
\(\dfrac{3}{5}+\dfrac{1}{2}+\dfrac{8}{15}\\ =\dfrac{3\times6}{5\times6}+\dfrac{1\times15}{2\times15}+\dfrac{8\times2}{15\times2}\\ =\dfrac{18}{30}+\dfrac{15}{30}+\dfrac{16}{30}\\ =\dfrac{49}{30}\\ \dfrac{6}{9}+\dfrac{14}{18}-\dfrac{5}{6}\\ =\dfrac{6\times2}{9\times2}+\dfrac{14}{18}-\dfrac{5\times3}{6\times3}\\ =\dfrac{12}{18}+\dfrac{14}{18}-\dfrac{15}{18}\\ =\dfrac{11}{18}\)
\(\dfrac{9}{20}-\dfrac{3}{5}:\dfrac{4}{1}\\ =\dfrac{9}{20}-\dfrac{3}{5}\times\dfrac{1}{4}\\ =\dfrac{9}{20}-\dfrac{3}{20}\\ =\dfrac{6}{20}\\ =\dfrac{3}{10}\)
\(\dfrac{1}{6}+\dfrac{2}{3}\times\dfrac{8}{9}\\=\dfrac{1}{6}+\dfrac{16}{27}\\ =\dfrac{1\times9}{6\times9}+\dfrac{16\times2}{27\times2}\\ =\dfrac{9}{54}+\dfrac{32}{54}\\ =\dfrac{41}{54}.\)
Tính (theo mẫu).
Mẫu: \(\dfrac{1}{2}-\dfrac{5}{12}=\dfrac{6}{12}-\dfrac{5}{12}=\dfrac{6-5}{12}=\dfrac{1}{12}\) |
a) \(\dfrac{3}{4}-\dfrac{1}{8}\) b) \(\dfrac{2}{6}-\dfrac{5}{18}\) c) \(\dfrac{2}{5}-\dfrac{3}{20}\)
a) \(\dfrac{3}{4}-\dfrac{1}{8}=\dfrac{6}{8}-\dfrac{1}{8}=\dfrac{6-1}{8}=\dfrac{5}{8}\)
b) \(\dfrac{2}{6}-\dfrac{5}{18}=\dfrac{6}{18}-\dfrac{5}{18}=\dfrac{6-5}{18}=\dfrac{1}{18}\)
c) \(\dfrac{2}{5}-\dfrac{3}{20}=\dfrac{8}{20}-\dfrac{3}{20}=\dfrac{8-3}{20}=\dfrac{5}{20}=\dfrac{1}{4}\)
Tính:
\(\dfrac{2}{5}+\dfrac{1}{5}\) \(\dfrac{2}{3}+\dfrac{5}{3}\) \(\dfrac{3}{8}+\dfrac{4}{8}\)
\(\dfrac{6}{9}+\dfrac{2}{9}\) \(\dfrac{12}{18}+\dfrac{7}{18}\) \(\dfrac{7}{4}+\dfrac{2}{4}\)
\(\dfrac{2}{5}+\dfrac{1}{5}=\dfrac{2+1}{5}=\dfrac{3}{5}\)
\(\dfrac{2}{3}+\dfrac{5}{3}=\dfrac{2+5}{3}=\dfrac{7}{3}\)
\(\dfrac{3}{8}+\dfrac{4}{8}=\dfrac{3+4}{8}=\dfrac{7}{8}\)
\(\dfrac{6}{9}+\dfrac{2}{9}=\dfrac{6+2}{9}=\dfrac{8}{9}\)
\(\dfrac{12}{18}+\dfrac{7}{18}=\dfrac{12+7}{18}=\dfrac{19}{18}\)
\(\dfrac{7}{4}+\dfrac{2}{4}=\dfrac{7+2}{4}=\dfrac{9}{4}\)
Rút gọn rồi tính.
a) \(\dfrac{2}{3}-\dfrac{2}{6}\) b) \(\dfrac{5}{6}-\dfrac{3}{18}\) c) \(\dfrac{8}{14}-\dfrac{2}{7}\) d) \(\dfrac{12}{20}-\dfrac{2}{5}\)
a) \(\dfrac{2}{3}-\dfrac{2}{6}=\dfrac{4}{6}-\dfrac{2}{6}=\dfrac{4-2}{6}=\dfrac{2}{6}=\dfrac{1}{3}\)
b) \(\dfrac{5}{6}-\dfrac{3}{18}=\dfrac{10}{18}-\dfrac{3}{18}=\dfrac{10-3}{18}=\dfrac{7}{18}\)
c) \(\dfrac{8}{14}-\dfrac{2}{7}=\dfrac{8}{14}-\dfrac{4}{14}=\dfrac{8-4}{14}=\dfrac{4}{14}=\dfrac{2}{7}\)
d) \(\dfrac{12}{20}-\dfrac{2}{5}=\dfrac{12}{20}-\dfrac{8}{20}=\dfrac{12-8}{20}=\dfrac{4}{20}=\dfrac{1}{5}\)
1/ \(\dfrac{x-4}{3}+2x=\dfrac{4x-2}{6}\)
2/ \(\dfrac{5x-2}{5}-2=\dfrac{1-2x}{3}\)
3/ \(\dfrac{x-2}{2}-\dfrac{2}{3}=x-1\)
4/ \(\dfrac{2x-1}{3}+\dfrac{3x-2}{4}=\dfrac{4x-3}{5}\)
5/ \(\dfrac{x-3}{9}-\dfrac{x+2}{6}=\dfrac{x+4}{18}-\dfrac{1}{2}\)
1: Ta có: \(\dfrac{x-4}{3}+2x=\dfrac{4x-2}{6}\)
\(\Leftrightarrow2x-8+12x=4x-2\)
\(\Leftrightarrow10x=6\)
hay \(x=\dfrac{3}{5}\)
2: Ta có: \(\dfrac{5x-2}{5}-2=\dfrac{1-2x}{3}\)
\(\Leftrightarrow15x-6-30=10-20x\)
\(\Leftrightarrow35x=46\)
hay \(x=\dfrac{46}{35}\)
3: Ta có: \(\dfrac{x-2}{2}-\dfrac{2}{3}=x-1\)
\(\Leftrightarrow3x-6-4=6x-6\)
\(\Leftrightarrow-3x=4\)
hay \(x=-\dfrac{4}{3}\)
1)\(\dfrac{x-4}{3}+2x=\dfrac{4x-2}{6}\)
\(\Leftrightarrow\dfrac{\left(x-4\right).2}{3.2}+\dfrac{2x.6}{6}=\dfrac{4x-2}{6}\)
\(\Rightarrow2x-8+12x=4x-2\\ \Leftrightarrow10x=6\\ \Leftrightarrow x=\dfrac{3}{5}\)
4: Ta có: \(\dfrac{2x-1}{3}+\dfrac{3x-2}{4}=\dfrac{4x-3}{5}\)
\(\Leftrightarrow40x-20+45x-30=48x-36\)
\(\Leftrightarrow37x=14\)
hay \(x=\dfrac{14}{37}\)
5: Ta có: \(\dfrac{x-3}{9}-\dfrac{x+2}{6}=\dfrac{x+4}{18}-\dfrac{1}{2}\)
\(\Leftrightarrow2x-6-3x-6=x+4-9\)
\(\Leftrightarrow-x-x=-5-12=-17\)
hay \(x=\dfrac{17}{2}\)
a, 1\(\dfrac{5}{18}\)+\(\dfrac{7}{25}\)-\(\dfrac{5}{18}\)+\(\dfrac{18}{25}\)-0, 75
b, \(\dfrac{2}{5}\).\(\dfrac{1}{3}\)-\(\dfrac{4}{3}\).\(\dfrac{2}{5}\)
c, (\(\dfrac{-1}{4}\)).( 6\(\dfrac{2}{11}\)) + 3 \(\dfrac{9}{11}\).(\(\dfrac{-1}{4}\))
d, 4. (-\(\dfrac{1}{2}\))\(^{3_{ }}\)-\(_{ }\)2. (\(\dfrac{-1}{2}\))\(^2\) + 3. (\(\dfrac{-1}{2}\)) + 1
e, \(\dfrac{1}{6}\)-(\(\dfrac{2}{3}\))\(^2\) + \(\dfrac{5}{18}\)
f, (\(\dfrac{4}{3}\)-\(\dfrac{3}{2}\))\(^2\)- 2.|-\(\dfrac{1}{9}\)| + (-\(\dfrac{5}{18}\))
e: \(=\dfrac{1}{6}-\dfrac{4}{9}+\dfrac{5}{18}=\dfrac{3-8+5}{18}=0\)
2.Tính giá trị biểu thức
a) ( 42 - \(\dfrac{5}{6}\) x \(\dfrac{36}{5}\)) : \(\dfrac{1}{2}\) + \(\dfrac{7}{6}\) b) \(\dfrac{18}{5}\) - \(\dfrac{1}{7}\) x 2 + \(\dfrac{1}{3}\)
a) ( 42- 6) : 1/2 + 7/6
= 36 : 1/2 + 7/6
= 72 + 7/6
= 439/6
b) 18/5 - 2/7 + 1/3
= 383/105
a) = ( 42 - 6) : 1/2 + 7/6
= 36 : 1/2 + 7/6
= 72 + 7/6
= 439/6
b) = 18/5 - 2/7 + 1/3
= 116/35 + 1/3
= 383/105
\(a.=\left(42-6\right):\dfrac{1}{2}+\dfrac{7}{6}\)
\(=36:\dfrac{1}{2}+\dfrac{7}{6}\)
\(=\)\(72+\dfrac{7}{6}\)
\(=\dfrac{439}{6}\)
Tính :
\(6.\dfrac{-5}{18};\dfrac{-13}{24}+\dfrac{-5}{21}.\dfrac{7}{25};\dfrac{-5}{13}-\dfrac{3}{26}.\dfrac{-2}{3};\left(\dfrac{2}{3}+\dfrac{-7}{6}\right).\left(\dfrac{3}{8}+\dfrac{-3}{24}\right)\)
\(6.-\dfrac{5}{18}=-\dfrac{5}{3}\)
\(-\dfrac{13}{24}+-\dfrac{5}{21}.\dfrac{7}{25}=-\dfrac{13}{24}+-\dfrac{1}{15}=-\dfrac{73}{120}\)
\(-\dfrac{5}{13}-\dfrac{3}{26}.-\dfrac{2}{3}=-\dfrac{5}{13}-\left(-\dfrac{1}{13}\right)=-\dfrac{4}{13}\)
\(\left(\dfrac{2}{3}+-\dfrac{7}{6}\right).\left(\dfrac{3}{8}+-\dfrac{3}{24}\right)=-\dfrac{1}{2}.\dfrac{1}{4}=\dfrac{1}{8}\)
Kết quả lần lượt của các phép tính là :
\(\dfrac{-5}{3}\) , \(\dfrac{-73}{120}\) , \(\dfrac{-4}{13}\) , \(\dfrac{-1}{8}\)
a, \(\dfrac{3}{2x+6}-\dfrac{x-6}{2x^2+6x}\)
b, \(\dfrac{x+2}{x-3}-\dfrac{x^2+6}{x^2-3x}\)
c, \(\dfrac{1}{9x-18}+\dfrac{16-7x}{72-18x}+\dfrac{5}{12x-24}\)
a.\(\dfrac{3}{2\left(x+3\right)}-\dfrac{x-6}{2x\left(x+3\right)}=\dfrac{3x-x+6}{2x\left(x+3\right)}=\dfrac{2x+6}{2x\left(x+3\right)}=\dfrac{1}{x}\)